2016
DOI: 10.1111/jcmm.12813
|View full text |Cite
|
Sign up to set email alerts
|

Renalase attenuates hypertension, renal injury and cardiac remodelling in rats with subtotal nephrectomy

Abstract: Chronic kidney disease is associated with higher risk of cardiovascular complication and this interaction can lead to accelerated dysfunction in both organs. Renalase, a kidney‐derived cytokine, not only protects against various renal diseases but also exerts cardio‐protective effects. Here, we investigated the role of renalase in the progression of cardiorenal syndrome (CRS) after subtotal nephrectomy. Sprague–Dawley rats were randomly subjected to sham operation or subtotal (5/6) nephrectomy (STNx). Two week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 51 publications
2
66
0
Order By: Relevance
“…The study of Li et al showed a significant increase in renalase expression with increasing oxidative stress in a mice model of ischemia-reperfusion injury, and it was suppressed by antioxidants 24) . In addition, it has been reported that renalase increases during ischemiareperfusion and has the effect of protecting organs [25][26][27] . There was also a significant increase in oxidative stress in this study, which is presumed to be ischemia of an organ or organ damage due to exercise 28) .…”
Section: Discussionmentioning
confidence: 99%
“…The study of Li et al showed a significant increase in renalase expression with increasing oxidative stress in a mice model of ischemia-reperfusion injury, and it was suppressed by antioxidants 24) . In addition, it has been reported that renalase increases during ischemiareperfusion and has the effect of protecting organs [25][26][27] . There was also a significant increase in oxidative stress in this study, which is presumed to be ischemia of an organ or organ damage due to exercise 28) .…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al [45] confirmed the beneficial effects of renalase supplementation on functional and histological alterations of kidney and heart, and investigated the underlying mechanism in a rat model with progressive renal injury. Furthermore, the authors [45] have demonstrated that the systematic delivery of renalase, a kidney-derived protein, attenuated both renal and cardiac fibrosis, improved renal function and prevented cardiac remodeling six weeks after renal ablation through its anti-inflammatory and anti-oxidant effects, inhibition of extracellular signal-regulated kinase (ERK) pathway, which indicate that renalase may play a crucial role in the interaction between kidney and heart. Taken together, these findings indicated renalase supplementation might protect renal injury through inhibiting inflammation activation and oxidative stress in remnant kidney.…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, cardiac tissue from CKD animals had increased matrix and TGF-β abundance and reduced matrix metalloproteinase-1. 24 It should also be noted that there are other CKD-related factors which play a role in the pathogenesis of uremic cardiomyopathy such as increased concentrations of FGF-23, Klotho deficiency and activation of the RAAS. 25,26 The effectiveness of RAAS inhibition in treatment of HF has been demonstrated in numerous clinical trials using ACEI or ARB therapy.…”
Section: Discussionmentioning
confidence: 99%